Photobleaching of pheomelanin increases its phototoxic potential: Physicochemical studies of synthetic pheomelanin subjected to aerobic photolysis. (11th December 2018) - Zadlo, Andrzej; Szewczyk, Grzegorz; Sarna, Michal; Camenisch, Theodore G.; Sidabras, Jason W.; Ito, Shosuke; Wakamatsu, Kazumasa; Sagan, Filip; Mitoraj, Mariusz; Sarna, Tadeusz
Abstract: Although melanin is a photoprotective pigment, its elevated photochemical reactivity could lead to various phototoxic processes. Photoreactivity of synthetic pheomelanin, derived from 5‐ S ‐cysteinyldopa (5SCD‐M) and its photodegradation products obtained by subjecting the melanin to aerobic irradiation with UV‐visible light, was examined employing an array of advanced physicochemical methods. Extensive photolysis of 5SCD‐M was accompanied by partial bleaching of the melanin, modification of its paramagnetic properties, and significant increase in the ability to photogenerate singlet oxygen. The changes correlated with a substantial decrease in the melanin content of benzothiazine (BT) units and increase of modified benzothiazole (BZ) units. Synthetically prepared BZ exhibited higher efficiency to photogenerate singlet oxygen than the synthetic BT, and the free radical form of BZ, unlike that of BT, did not show measurable spin density on nitrogen atom, which was confirmed by quantum chemical calculations. Formation of modified BZ units in the photobleached 5SCD‐M is responsible for the paramagnetic and photochemical changes of the melanin and its elevated phototoxic potential. Given a relatively constant pheomelanin–eumelanin ratio, such undesirable changes could occur in individual of all skin types.